Maternal arterial elasticity in the first trimester as a predictor of birthweight. (3rd July 2016) - O'Connor, Clare; O'Higgins, Amy; Segurado, Ricardo; Turner, Michael J.; Stuart, Bernard; Kennelly, Máireád M.
Abstract : The early detection of foetal growth restriction and macrosomia is an important goal of modern obstetric care. Aberrant foetal growth is an important cause of perinatal morbidity and mortality. Current modalities for detecting the abnormal foetal growth are often inadequate. Pulse wave analysis using applanation tonometry is a simple and non-invasive test that provides information about the cardiovascular system. Arterial elasticity has previously been implicated in the pathophysiology of pre-eclampsia and cardiovascular disease. Our study examined the relationship between maternal arterial elasticity and birthweight by using pulse wave analysis. We discovered that increased large artery elasticity predicted a larger baby at birth. Large artery elasticity therefore has the potential to act as a useful screening tool which may help in the prediction of women who are at risk of aberrant foetal growth.